Evaluation and redesigning of DARICH's Training Module on its program on gangs - Parreño, Edjan S.
The Davao Advocates of the Rights of the Child (DARICH), a non-government organization is conducting programs such as seminars, which aims to help gang members cope with life and as a result, lessen the prevalence of gangs in Davao City. The organization was able to identify the general profile of the participants and found out that these participants do not have the capability of producing wealth that would satisfy their basic needs like food, clothing, and shelter. However the program intended for gangs never dealt with these basic needs: instead, it only focuses in the psychosocial aspect of a person. The program was also heavy on lecture and has less activity during the delivery of the lessons. This study, Evaluation and Redesigning of DARICH?s Training Module on its Program on Gangs filled in the deficiency of the program by subjecting the lessons of the training module to the Experiential Learning Cycle and Maslow?s Hierarchy of Needs. Gaps like the lack of activities during the lessons were seen. The objective of the lessons and the added activities prior to it are almost the same. With the help of group dynamics brought by these activities, participants would really own learning. Therefore, these lessons and activities must be handled by professional such as psychologists. After these lessons, a pangkabuhayan lesson must be integrated to the whole program to help the participants satisfy their basic needs.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Speech/Corporate Communication